Research for marketing - Baker, Michael J. (Henry Stewart Talks, 2012)
The scope and nature of marketing research, Quantitative or qualitative?, Data collection, Secondary sources, Primary sources, Probability samples, Non-probability samples, Surveys, Data reduction and analysis
Reviewed at 2020/03/30